Greenland in Arctic Security (De)securitization Dynamics under Climatic Thaw and Geopolitical Freeze - Jacobsen, Marc; Wæver, Ole; Gad, Ulrik Pram (University of Michigan Press, 2024)
Greenland has increasingly captivated imaginations around the globe. Yet, while it is central to the Arctic region, its role has been poorly understood. Greenland in Arctic Security delivers a comprehensive overview of how security dynamics unfold in and in relation to Greenland. Each individual chapter analyzes specific discourses and dynamics pertaining to hard or soft security questions. These span from great power interests in geostrategic infrastructure to domestic debates centered on promoting and protecting Greenland identity when engaging with the outside world. In addition, the book offers perspectives on other security questions that have been catalyzed by the effects of climate change. By combining these different analyses, Greenland in Arctic Security provides new, theoretically informed discussions on how security politics can manifest across different scales and territorial borders. At times, these politics can have consequences beyond their original intent. With Greenland geopolitics and securitization theory of current interest to political and academic debates, this book offers timely insights for readers.